Bucin itu Bukan Cinta: Mindful Dating for Flourishing Relationship - Dwijayani, Ni Komang Karmini (Widya Cakra: Journal of Psychology and Humanities; Vol 1 No 1 (2020): Volume 1 Nomor 1 Tahun 2020 - Widya CakraDO - 10.24843/widyacakra.2020.v1.i1.p69189, 2020)
Love is a natural human need. Adolescence implements love in romantic relationship specifically in dating. But, the unstable emotion in adolescent bring “fool of love” behavior. This term refers to someone who over behavior to their partner. “Fool of love a.k.a bucin” can develop become financial extortion, dating violence, premarital sexual intercourse, suicide, and other negative effects. Mindful dating can help adolescent avoid negative things from dating. Parents and peer support also necessary as external factor that can build positive bounding. This article use applied literature study that revealed dating and love concept due to psychological perspective. Various study shows that there are many positive things and benefits from dating relationship and its relation to mindfulness. Mindful dating leads couples to minimize negative effect that become challenges during dating that can guide adolescent achieving flourishing relationship.